Analysis of village apparatus competencies, society participations, the village government organizational commitment, and village financial reporting compliance effects towards village financial management accountability at Amahai District, Central Mal - Sososutiksno, Ch.; Usmany, P.; Mayaut, Marla (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research purpose is to empirically test the village apparatus competencies, society participations, the village government organizational commitment, and financial reporting compliance towards financial management accountability at Amahai District, Central Maluku Regency. The population of this research is all village financial managements at Amahai District, Central Maluku Regency, which consist of 14 villages. The samples are the Chief, Secretary, Treasurer, and the Head of Public Welfare of the villages. The sampling technique used the purposive sampling method and the analysis modeling used Classical Assumption Test, Validation Tests, Reliability Test, Descriptive Statistic, and hypothesis by using multiple linear regression analysis. In conclusion, the analysis result explains that the variable of village apparatus competencies influenced the villages financial management accountability, and the financial reporting compliance effects positively and significantly towards the villages financial management accountability at Amahai District, Central Maluku Regency.